Routine follow-up transjugular liver biopsy in Fontan patients: technical considerations and safety of an initial case series and literature review - Mandilaras, Guido; Meyer, Zora; Mühlberg, Richard; Braun, Annabell; Haas, Nikolaus A.; Jakob, Andre; Dalla Pozza, Robert; Wildgruber, Moritz; Fischer, Marcus (Frontiers in Pediatrics, 2023)
Introduction: Patients with Fontan palliation are susceptible to congestive hepatopathy and Fontanassociated liver disease (FALD) due to hemodynamic changes. Staging of liver fibrosis involves various methods, including invasive biopsy. Transjugular liver biopsy (TJLB) offers a less invasive alternative, enhancing liver disease surveillance in routine cardiac catheterization. We detail the technical aspects, share initial outcomes, and discuss existing literature.Methods/Results: During routine follow-up cardiac catheterization indicated by hemodynamic or clinical alterations, four patients with univentricular Fontan-circulation, aged between 16 and 26 years, as well as three patients with biventricular circulation, underwent TJLB during routine surveillance catheterization. The examinations were performed under conscious sedation and local anesthesia, without the need for general anesthesia. Jugular access was obtained at the site of liver localization, and a 5 F multipurpose catheter was inserted into the liver veins. After hand angiography to delineate the local hepatic venous anatomy, an exchange wire was used to place the bioptome, and three consecutive biopsies were performed. There were no complications, especially no perforation or bleeding. Technical success was 100%, with all obtained samples being appropriate for histopathological diagnostics. The total additional procedure time was less than 20 minutes. Conclusion: TJLB is an attractive alternative method for obtaining liver specimens in the scope of FALD care. We believe that it should be performed during routine hemodynamic evaluations in Fontan patients and can be performed safely with very low additional time expenditure. As the biopsy site is intravascular, the risk of external bleeding or hematoma is significantly reduced despite the high intrahepatic pressures and the usually impaired coagulation profile in these patients. Based on our initial experience and the lower complication rates than other techniques, TJLB should be considered as a standard approach in these patients and used more often during the long-term followup of Fontan patients; it can be performed in the same setting whenever hemodynamic assessment of patients with congenital heart defects is required.